PENGARUH BENTUK TELUR PUYUH TERHADAP PENENTUAN JENIS KELAMIN ANAK PUYUH (Coturnix-coturnix japonica) (MARSEGU : Jurnal Sains dan Teknologi, 2025)
This research aims to test whether there is an effect of quail egg shape on determining the sex of quail chicks produced when hatched. This research was conducted at a quail farm located in Toisapu hamlet, Hutumuri Village, Ambon City on March 29 - April 19, 2025. The research method used a completely randomized design (CRD) with 2 treatments and 8 replications. A total of 192 hatching eggs were classified based on the egg shape index (oval category with a value of 69-77, round category with a value >77). The treatment groups formed were P1 (oval) and P2 (round). The variables observed included hatchability, mortality, and sex of quail chicks. Data were analyzed using ANOVA for hatchability, and mortality variables and Chi Square test for sex. The results showed that egg shape had no significant effect on hatchability, mortality, and sex produced. This study concluded that egg shape cannot be used as an indicator to predict the sex of quail chicks that will hatch.